The implementation of personal protective equipment (PPE) in construction site in Selangor / Siti Khairulnisa Mohd Khalid - Mohd Khalid, Siti Khairulnisa (Faculty of Architecture, Planning and Surveying, 2015)
The construction industry has been recognized as one of the hazardous industries. Although there is an improvement of the safety performance and increase in safety awareness in this industry, the accident rate is still one of the highest across all sectors. Besides causing human tragedy and economic losses, construction accidents also affect the productivity and reputation of the construction industry. The purpose of this study was to identify the importance of enforcing the used of PPE, to examine the implementation of PPE and to measure the awareness of using PPE in construction site. A quantitative research study was done using a questionnaire, interview session and the observation was made as a data gathering tool on workers who are exposed to occupational injuries and who use PPE for their protection. The findings revealed that even though workers were using PPE but there is lack of enforcement and the workers still got occupational injuries and illnesses. They also had problems with their protective equipment like incompatible types of PPE. In some instances unavailability of or unsuitable PPE posed challenges to these workers.